A new species of Websterinereis from the Gulf of California and redescription of Websterinereis foli (Fauvel, 1930) (Annelida, Nereididae) - De León González, Jesús Ángel; Balart, Eduardo F. (2016)
A new species of Websterinereis Pettibone, 1971, W. pettiboneae sp. n. is described from La Paz Bay, Gulf of California, Mexico. This species is similar to W. foli (Fauvel, 1930) in the neuropodial falcigers shape, but can be separated by the tentacular cirri length, notopodial prechaetal lobe shape, and the size of the notopodial dorsal and ventral ligules on posterior parapodia. Websterinereis foli is redescribed based upon type material. Additional observations on the inter-annual density variation of W. pettiboneae sp. n. during a four-year study are also provided. A key to all species of Websterinereis is included.